2017
DOI: 10.3390/antiox6040076
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine and Superoxide Dismutase 1 Synergistically Counteract Alzheimer’s Disease Features Progression in TgCRND8 Mice

Abstract: Recent evidence emphasizes the role of dysregulated one-carbon metabolism in Alzheimer’s Disease (AD). Exploiting a nutritional B-vitamin deficiency paradigm, we have previously shown that PSEN1 and BACE1 activity is modulated by one-carbon metabolism, leading to increased amyloid production. We have also demonstrated that S-adenosylmethionine (SAM) supplementation contrasted the AD-like features, induced by B-vitamin deficiency. In the present study, we expanded these observations by investigating the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…The biosynthesis of epinephrine, serotonin, and dopamine is independently influenced by a universal methyl donor, S-adenosylmethionine (SAM), a critical intermediate in the methionine-cycle [ 140 , 155 , 156 , 157 , 158 , 159 , 160 ] ( Figure 5 ). Consequently, several studies have shown that a deficiency in vitB 6 correlates with a deficiency in folate and cobalamin [ 138 , 140 , 153 , 154 ].…”
Section: Vitamin B 6 and Its Involvement In Celmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis of epinephrine, serotonin, and dopamine is independently influenced by a universal methyl donor, S-adenosylmethionine (SAM), a critical intermediate in the methionine-cycle [ 140 , 155 , 156 , 157 , 158 , 159 , 160 ] ( Figure 5 ). Consequently, several studies have shown that a deficiency in vitB 6 correlates with a deficiency in folate and cobalamin [ 138 , 140 , 153 , 154 ].…”
Section: Vitamin B 6 and Its Involvement In Celmentioning
confidence: 99%
“…Methylation of homocyteine to methionone depends on two other important vitamins, cobalamin (vitB 12 ), and folate (vitB 9 ), where PLP-dependent enzymes such as SHMT, which converts tetrahydrofolate (THF) to 5, 10-methylene tetrahydrofolate, are involved ( Figure 6 ). Elevated levels of homocysteine, otherwise known as hyperhomocysteinemia, are recognized as a cardiovascular risk factor; are a predictor of primary-cause vascular mortality; and have also been associated with mental retardation, seizures, depression, schizophrenia, and cognitive impairment [ 138 , 153 , 160 , 161 ]. Homocysteine can be converted in three different ways in the cell.…”
Section: Vitamin B 6 and Its Involvement In Celmentioning
confidence: 99%
“…TgCRND8 mice (a mouse model of AD, Table 1 1 ) on this diet show reduced DNA methyltransferase activity, hypomethylation of the Psen1 promoter, increased PSEN1 expression, and increased level of amyloid plaques ( Fuso et al, 2008 ; Fuso et al, 2011 ). Supplementing with SAM reduced expression of Psen1 and Bace1 in the TgCRND8 mice, and the development of amyloid plaques was decreased ( Fuso et al, 2012 ; Cavallaro et al, 2017 ). Together, these data provide solid support for the idea that an imbalance in one-carbon metabolism results in reduced DNA methylation at the Psen1 gene, increasing PSEN1 expression and activity, and contributes to the build-up of amyloid deposits.…”
Section: Dna Methylation Changes Associated With Alzheimer’s Diseasementioning
confidence: 99%
“…Pathological and experimental studies suggested that oxidative stress has a pivotal role in the occurrence and progression of Alzheimer's disease (AD) and other degenerative neurological diseases 1,2 . There are two ways to measure oxidative stress in human brain in vivo.…”
Section: Introductionmentioning
confidence: 99%